A principles-based approach to evaluating family engagement group strategies: Lessons from a IV-E Waiver Demonstration Project. Issue 4 (8th August 2022) - Perry, Marlo A.; Rauktis, Mary E.; Cahalane, Helen
ABSTRACT: Family engagement conferences are a commonly utilized strategy in child welfare to empower families to make decisions for the safety and well-being of their own children. However, there is mixed evidence about their effectiveness, in large part due to the lack of detail about what is actually occurring in those conferences. Using data from a Title IV-E waiver, the present study utilized a principles-focused evaluation approach to explore how well a set of different family engagement models employed across six county child welfare systems adhered to a common set of principles. Findings suggest that the specific name or branding of a family engagement model – and their model-specific practices, such as private family time – matters less than the general components of practice and fidelity with which they are carried out. Further, this study provides evidence for the ability to conduct an evaluation of similar – but not identical – conferencing models across multiple sites.